2-glyceryl monopalmitate in virgin and pomace olive oil during refining processes. (December 2020) - Jabeur, Hazem; Marrakchi, Fatma; Drira, Malika; Ghodhbani, Imed; Bouaziz, Mohamed
Abstract: The level of 2-glyceryl monopalmitate (2-GMP) measures adulteration in olive oil with esterified oils. However, there are genuine refined olive and refined olive-pomace oils that do not meet the specifications of the standard set by the International Olive Council. For this reason, there is a need to investigate the factors that affect 2-GMP levels in olive and in olive pomace oil. The results showed a range for palmitic acid from 9.91 to 18.5% in different olive oil varieties and with it a progressive rise in 2-GMP from 0.59 to 0.92%. In addition, other oils, rich in palmitic acid, have higher percentages (7.82 and 8.27% of 2-GMP in coprah and palm oil, respectively). On the other hand, higher contents of 2-GMP were found in refined oils after physical refining compared to chemical refining. Interesterification reactions were increased because of the high steam distillation temperatures and residence time along with the higher amounts of free fatty acids and the presence of mono- and di-glycerides. An experimental design, central composite design, was used to find a model that optimizes temperature and residence time to minimize 2-GMP and showed that the best condition was 180 °C for 175 min. Graphical abstract: Image 1 Highlights: Identification and quantification of 2-glyceryl monopalmitate in virgin and pomace olive oil with esterified oils. Both deodorization temperature and residence time increased the palmitic acid of the 2-position of the triacylglycerols. The industrial deodorization step optimized using CCD keeps the 2-glyceryl monopalmitate content at a low level.